Policy issues for long-term growth of fertilizer use in Bangladesh - Desai, Gunvant M. (International Food Policy Research Institute, 1987)
This paper discusses policy issues relevant to sustained rapid growth in Bangladesh's fertilizer consumption. The second section is an overview of fertilizer consumption as it has evolved over the years. It also provides a comparative perspective on the performance of Bangladesh among developing countries. The third section discusses policy requirements of long-term rapid growth in fertilizer use, keeping in mind various features of, and major forces behind, the past growth.